2017
DOI: 10.31234/osf.io/gxvwk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Attention Bias Modification for Obsessive-Compulsive Disorder: A Randomized Controlled Trial

Abstract: There is evidence that attention bias modification trainings (ABMT) based on the dot-probe task are a promising therapeutic approach for several anxiety disorders. However, little is known about the malleability of attention bias in obsessive-compulsive disorder (OCD) and its impact on OCD symptoms. The present study tested this hypothesis using an online ABMT designed to train attention away from OCD-related stimuli. We hypothesized that ABMT would reduce attention bias and OCD symptoms. Participants were ran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Studies revealed that Cognitive Behavioral Therapy (CBT) is effective in improving OCD in adults and non-adults (Salemink, Wolters, & de Haan, 2015); however, this treatment is not acceptable or accessible for numerous patients (Black & Grisham, 2018). Studies demonstrated that only 5%-25% of patients with OCD have access to CBT (Amir et al, 2015;Andersson et al, 2012) and from those, only 40%-60% respond to the treatment (Habedank, Lennartz, Arslan, & Ertle, 2017;Williams & Grisham, 2013). Therefore, it is necessary to conduct further research for the development and assessment of new treatment methods for OCD.…”
Section: Introduction Bsessive-compulsivementioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealed that Cognitive Behavioral Therapy (CBT) is effective in improving OCD in adults and non-adults (Salemink, Wolters, & de Haan, 2015); however, this treatment is not acceptable or accessible for numerous patients (Black & Grisham, 2018). Studies demonstrated that only 5%-25% of patients with OCD have access to CBT (Amir et al, 2015;Andersson et al, 2012) and from those, only 40%-60% respond to the treatment (Habedank, Lennartz, Arslan, & Ertle, 2017;Williams & Grisham, 2013). Therefore, it is necessary to conduct further research for the development and assessment of new treatment methods for OCD.…”
Section: Introduction Bsessive-compulsivementioning
confidence: 99%
“…Several studies revealed that CBMI and CBMA reduce cognitive biases in individuals with OCD. CBMA only reduces attention bias towards OCD-related stimuli, and presents no significant effect on the severity of OCD (Habedank et al, 2017;Mohsenpourian, Nokani, Jamilian, & Ghasemi, 2019;Rouel & Smith, 2018); while CBMI not only impacts interpretation bias, but also reduces OCD severity (Black & Grisham, 2016;Clerkin & Teachman, 2011;Dalir, Alipour, Zare, & Farzad, 2016). CBMI, in comparison with the main treatment of OCD, i.e.…”
mentioning
confidence: 99%